1992
DOI: 10.3406/hel.1992.2340
|View full text |Cite
|
Sign up to set email alerts
|

Sur l'adjectif dans la tradition grammaticale tamoule

Abstract: : The Tamil tradition does not recognise adjectives among its morphological classifications, even if it is concerned with a certain number of problems which I would describe as adjectival. Such problems can be grouped : 1. in relation to a common semantic problem (see the term panpu), and 2. in relation to paraphrastic strategies which vary from grammarian to grammarian, and which link the different elements of what I would term the adjectival paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…clul.ulisboa.pt/en/10-research/867-crioulos-de-base-portuguesa-no-espaco-dravidico-diacronia-esincronia. 42 For example, manuscript grammars produced by the French, such as the Dictionaire et Gramaire François Tamovl (1743) written by Dominique de Valence (James 2000: 123) and Tolkāppiyam written in verse during the early years of the Christian era by Tolkāppiyanār (see Chevillard (1992aChevillard ( , 1992bChevillard ( , 2000Chevillard ( : 191-200, 2013Chevillard ( , 2014. The grammatical tradition established by Pāṇini was not transmitted, for example, in the later Hindi grammatical tradition "which largely resulted from the importation of Western approaches to grammar" (Shapiro 2000: 178), but rather influenced early grammarians of Dravidian languages.…”
Section: Portuguese As Metalanguage Of Grammaticisationmentioning
confidence: 99%
See 1 more Smart Citation
“…clul.ulisboa.pt/en/10-research/867-crioulos-de-base-portuguesa-no-espaco-dravidico-diacronia-esincronia. 42 For example, manuscript grammars produced by the French, such as the Dictionaire et Gramaire François Tamovl (1743) written by Dominique de Valence (James 2000: 123) and Tolkāppiyam written in verse during the early years of the Christian era by Tolkāppiyanār (see Chevillard (1992aChevillard ( , 1992bChevillard ( , 2000Chevillard ( : 191-200, 2013Chevillard ( , 2014. The grammatical tradition established by Pāṇini was not transmitted, for example, in the later Hindi grammatical tradition "which largely resulted from the importation of Western approaches to grammar" (Shapiro 2000: 178), but rather influenced early grammarians of Dravidian languages.…”
Section: Portuguese As Metalanguage Of Grammaticisationmentioning
confidence: 99%
“…The second one relates to the sheer amount of linguistic data which, thanks to the linguistic fieldwork carried out by missionaries before and others later, reached Europe, 57 Chevillard (1992a: 78-79) offers a detailed chronology of Beschi's works (See Babington 1822, Horst 1806, Mahon 1848. For further details about G. C. Beschi see also Chevillard (1992bChevillard ( , 2017, James (2000), and Meenakshisundaran (1974: 28-33 Brahmins' language] in the address to the reader. They identified that linguistic variation was determined by the speakers belonging to different social groups (diastratic variation) as well as the medium and contexts of communication (diamesic and diaphasic variations).…”
Section: The Model Of Reference In the Grammaticisation Of Indian Lanmentioning
confidence: 99%